Modified barrier method for optimal power flow problem - De Sousa, Vanusa A.; Baptista, Edméa C. [UNESP]; Da Costa, Geraldo R.M. (Institute of Electrical and Electronics Engineers (IEEE), 2004)
In this paper is presented a new approach for optimal power flow problem. This approach is based on the modified barrier function and the primal-dual logarithmic barrier method. A Lagrangian function is associated with the modified problem. The first-order necessary conditions for optimality are fulfilled by Newton's method, and by updating the barrier terms. The effectiveness of the proposed approach has been examined by solving the Brazilian 53-bus, IEEE118-bus and IEEE162-bus systems.
Keywords: Modified barrier function; Newton's method; Nonlinear programming; Optimal power flow; Power system planning.; Electric potential; Electric power generation; Lagrange multipliers; Mathematical models; Numerical methods; Optimization; Strategic planning; Vectors; Modified barrier functions; Optimal power flow (OPF); Power system planning; Electric power systems